2012
DOI: 10.1111/j.1365-2249.2012.04621.x
|View full text |Cite
|
Sign up to set email alerts
|

X chromosome gene methylation in peripheral lymphocytes from monozygotic twins discordant for scleroderma

Abstract: SummaryScleroderma (SSc) is a rare connective tissue disease characterized by fibrosis, microvasculopathy and autoimmune features. The role of genetics is limited in SSc, as suggested by similar concordance rates in monozygotic and dizygotic twin pairs, while environmental factors may act through epigenetic changes, as demonstrated for specific genes. Further, sex chromosome changes have been reported in SSc and may explain the female preponderance. In the present study we compared the methylation profile of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 71 publications
1
30
3
Order By: Relevance
“…56 Supporting this hypothesis, the DNA methylation profile of peripheral blood mono nuclear cells from monozygotic twins discordant for SSc showed that only X chromosome sites were consistently either hypermethylated or hypomethylated. 57 However, these observations fail to demonstrate the functional consequence of the altered DNA methylation pattern on the phenotype of peripheral leukocytes from patients with SSc. Another report indicated that increased DNA methylation of regulatory sequences in FOXP3 from CD4 + T cells from patients with SSc affected the expres sion of this key transcription factor, which is required for the generation of regulatory T cells.…”
Section: Box 2 | Epigenetic Mechanismsmentioning
confidence: 96%
“…56 Supporting this hypothesis, the DNA methylation profile of peripheral blood mono nuclear cells from monozygotic twins discordant for SSc showed that only X chromosome sites were consistently either hypermethylated or hypomethylated. 57 However, these observations fail to demonstrate the functional consequence of the altered DNA methylation pattern on the phenotype of peripheral leukocytes from patients with SSc. Another report indicated that increased DNA methylation of regulatory sequences in FOXP3 from CD4 + T cells from patients with SSc affected the expres sion of this key transcription factor, which is required for the generation of regulatory T cells.…”
Section: Box 2 | Epigenetic Mechanismsmentioning
confidence: 96%
“…RORγ and RORγτ are gene products of RORC1 and RORC2 genes, respectively, with RORγτ being strongly involved in polarization of Th cells towards Th17. Epigenetic regulation of T-cell-specific transcription factors by methylation of regulatory CpG sites has been suggested to influence the pathogenesis of SSc [21,22,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…We are convinced that environmental factors are central to SSc pathogenesis and may act through epigenetic changes, particularly DNA methylation [52]. Our group has previously demonstrated that the methylation profile of the X chromosome in MZ discordant and concordant SSc twins varies according to disease status, thus suggesting that different methylation profiles in MZ twin pairs may constitute candidates for SSc susceptibility [53]. In SSc, hypermethylated CpG islands are found in the Fli1 promoter, which is a transcription factor that inhibits collagen production.…”
Section: Systemic Sclerosismentioning
confidence: 94%